2021
DOI: 10.1111/jsap.13467
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of caudal superficial epigastric axial pattern flaps in dogs and cats: 70 cases (2007‐2020)

Abstract: Objectives To describe the outcome and complications associated with the use of caudal superficial epigastric axial pattern flaps in dogs and cats. Material and Methods Multicentre retrospective review and descriptive study of clinical records of dogs and cats having undergone caudal superficial epigastric axial pattern flaps between 2007 and 2020. Data retrieved included signalment, aetiology of surgical defect, tumour type, presence/absence of clean surgical margins, presence/absence of post‐operative wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Nevertheless, all flaps healed completely with only one requiring further surgical intervention. In the present study, the complication rate was lower than is reported following thoracodorsal (80%), caudal auricular (63%), genicular (63%), caudal superficial epigastric (67%) and superficial brachial (100%) APF (Aper & Smeak 2003, Emmerson et al 2019, Proot et al 2019, Forster et al 2022, Villedieu et al 2022. The reason for the lower complication rate is unknown, but it could be speculated that being the CrSE APF is generally shorter and smaller than other flaps, the risk of vascular embarrassment post-transposition might be lower.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Nevertheless, all flaps healed completely with only one requiring further surgical intervention. In the present study, the complication rate was lower than is reported following thoracodorsal (80%), caudal auricular (63%), genicular (63%), caudal superficial epigastric (67%) and superficial brachial (100%) APF (Aper & Smeak 2003, Emmerson et al 2019, Proot et al 2019, Forster et al 2022, Villedieu et al 2022. The reason for the lower complication rate is unknown, but it could be speculated that being the CrSE APF is generally shorter and smaller than other flaps, the risk of vascular embarrassment post-transposition might be lower.…”
Section: Discussioncontrasting
confidence: 49%
“…Several APFs have been described in the literature and are named after the direct cutaneous artery that supplies each angiosome (Pavletic 1981, Kostolich & Pavletic 1987, Henney & Pavletic 1988, Smith et al 1991, Degner et al 1994, Fahie & Smith 1997, Anderson et al 2004, Saifzadeh et al 2005, Field et al 2015, Proot et al 2019, Forster et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…For long-term resolution of an axillary wound, antimicrobial therapy is important, and particularly when reconstruction with a skin flap is planned, as infection is one of the most common complications observed. 23 As mentioned earlier, the reported microorganisms populating chronic axillary wounds are varied. While there are no specific guidelines regarding antimicrobial treatment of wounds in veterinary medicine, the following antimicrobial stewardship guidelines should be followed: < taking measures to prevent common diseases; < using evidence-based approaches when making decisions about antimicrobial drugs; < using antimicrobial drugs wisely and carefully.…”
Section: Antimicrobial Treatmentmentioning
confidence: 96%
“…For long-term resolution of an axillary wound, antimicrobial therapy is important, and particularly when reconstruction with a skin flap is planned, as infection is one of the most common complications observed. 23 …”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
See 1 more Smart Citation